2019
DOI: 10.18280/ts.360505
|View full text |Cite
|
Sign up to set email alerts
|

A Tweakable Image Encryption Algorithm Using an Improved Logistic Chaotic Map

Abstract: This paper aims to improves the chaotic behavior of classical logistic chaotic map for image encryption. First, this classical technique was enhanced, and the effectiveness of the improved technique was verified by the bifurcation diagram and Lyapunov exponent, in comparison to the classical technique. On this basis, an efficient tweakable image encryption algorithm was proposed to protect the security of digital image transmission. The proposed algorithm adopts a confusion-diffusion architecture. With the aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Step 2: Chaotic matrix S is converted into integer form to produce diffusion matrix D as in Equation (16).…”
Section: Diffusion Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Step 2: Chaotic matrix S is converted into integer form to produce diffusion matrix D as in Equation (16).…”
Section: Diffusion Phasementioning
confidence: 99%
“…It has been found that the main problems of 1D chaotic maps are: (a) the chaotic range is relatively limited; (b) there is non-uniform distribution of data of the output chaotic sequences; (c) the proposed key is not sufficiently secure; (d) the attacks on random sequences are fast with a rather low computational cost. Consequently, some researchers have suggested an improved version of existing 1D chaotic maps in order to overcome 1D chaotic maps problems [14][15][16][17][18], while other researchers have suggested some novel 1D chaotic maps [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Logistics heat has always been a hot topic in the research of the logistics industry [11][12][13][14][15]. Lan and Zhong [16] carried out entropy analysis and classification of the data collected from online logistics heat maps, aiming to optimize the spatial pattern of logistics in economic development zones.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, researchers have developed many image encryption schemes based on different theories like: chaos [3][4][5][6][7][8], Deoxyribonucleic Acid (DNA) [9][10][11][12] and Substitution-Box (S-box) [13][14][15]. These schemes were designed to solve different problems.…”
Section: Introductionmentioning
confidence: 99%